Through modulation of cardiac Ca2+ handling, UCP2 affects cardiac electrophysiology and influences the susceptibility for Ca2+‐mediated arrhythmias. Issue 6 (1st June 2017) - Larbig, Robert; Reda, Sara; Paar, Vera; Trost, Andrea; Leitner, Johannes; Weichselbaumer, Stephanie; Motloch, Karolina A.; Wernly, Bernhard; Arrer, Andreas; Strauss, Benjamin; Lichtenauer, Michael; Reitsamer, Herbert A.; et al.
Abstract : New Findings: What is the central question of this study? Knockdown of UCP2 reduces mitochondrial Ca 2+ uptake. This suggests that Ucp2 knockout mice need to have additional effects on cytosolic Ca 2+ handling to prevent Ca 2+ overload. However, the specific mechanisms and their impact on cardiac electrophysiology remain speculative. What is the main finding and its importance? In Ucp2 knockout mice, decreased mitochondrial Ca 2+ uptake is compensated for by functional inhibition of L‐type Ca 2+ channels and resultant shortening of action potential duration. UCP2‐dependent modulations have a major impact on cardiac electrophysiology, resulting in alterations of ECG characteristics and a higher susceptibility to Ca 2+ ‐mediated ventricular arrhythmias. Uncoupling protein 2 (mitochondrial, proton carrier) (UCP2) belongs to a superfamily of mitochondrial ion transporters. Owing to its beneficial influence on production of reactive oxygen species, it is suggested to reduce cardiac ischaemia–reperfusion injury. Recent studies have uncovered its ability to regulate mitochondrial Ca 2+ uptake and therefore to influence cardiac cytosolic Ca 2+ handling, indicating compensatory pathways to avoid toxic Ca 2+ overload in Ucp2 knockout ( Ucp2 −/− ) mice. However, the specific mechanisms and their impact on cardiac electrophysiology remain speculative. Molecular analyses, whole‐cell patch clamp in cardiomyocytes and ECG studies were performed in Ucp2 −/− and wild‐type (WT) control mice. Furthermore, to explore the impact on cardiac arrhythmogenicity, ECG monitoring was performed in basal conditions and during Ca 2+ ‐mediated stress using Bay K 8644. Although cardiac ryanodine receptor 2, NCX1, L‐type Ca 2+ channel (LTCC) and SERCA2a expression were not altered, Ucp2 −/− mice revealed major variations in cardiac electrophysiology. The LTCC current and APD90 were decreased in Ucp2 −/− mice, indicating compensatory mechanisms. Furthermore, in Ucp2 −/− mice, an increased slope factor of action potential upstrokes and more hyperpolarized resting membrane potential were measured, suggesting variations in cardiac excitability. In agreement with alterations of cellular physiology in Ucp2 −/− mice, reductions in PR and QRS as well as shortening of the QTc interval were noted in ECG recordings. Importantly, an increased incidence of cellular after‐depolarizations and more pronounced susceptibility to Ca 2+ ‐mediated arrhythmias were observed. Furthermore, although expression of UCP3 was not different, levels of PRMT1 were significantly higher in Ucp2 −/− mice. Our observations indicate compensatory mechanisms by which Ucp2 −/− mice prevent toxic cytosolic Ca 2+ overload. UCP2‐dependent modulations have a major impact on cardiac electrophysiology and influence susceptibility to Ca 2+ ‐mediated ventricular arrhythmias. Abstract :